Engineers and global economy in the 21st century: a conceptual analysis - Usmani, Tasneem; Nor Azmi, Johari (Universiti Malaysia Perlis, 2009)
Organized by Centre for Communication Skills and Entrepreneurship UniMAP in collaboration with The Ministry of Higher Education Malaysia, 5th - 6th December 2008 at Putra Palace Hotel, Perlis.